Fundamentals to clinical application of nanoparticles in cancer immunotherapy and radiotherapy - Selvaraja, Vinodh Kumar (Ecancermedicalscience, 2020)
Cancer immunotherapy has made rapid progress over the past decade leading to high enthusiasm and interest worldwide. Codelivery of immunomodulators with chemotherapeutic agents and radioisotopes has been shown to elicit a strong and sustained immune response in animal models. Despite showing promising results in metastatic and recurrent cancers, the utilisation of immunotherapy in clinical settings has been limited owing to uncertainties in elicited immune response and occurrence of immune-related adverse events. These uncertainties can be overcome with the help of nanoparticles possessing unique properties for the effective delivery of targeted agents to specific sites. Nanoparticles play a crucial role in the effective delivery of cancer antigens and adjuvants, modulation of tumour microenvironment, production of long-term immune response and development of cancer vaccines. Here, we provide a comprehensive summary of nanotechnology-based cancer immunotherapy and radiotherapy including basics of nanotechnology, properties of nanoparticles and various methods of employing nanoparticles in cancer treatment. Thus, nanotechnology is anticipated to overcome the limitations of existing cancer immunotherapy and to effectively combine various cancer treatment modalities.